Obraz duszpasterza w komentarzach św. Augustyna do J 10, 1-17 i 21, 15-17 - Wygralak, Paweł (Vox Patrum, 2013)
The article presents the teaching of St. Augustine on priesthood – priests, their attitudes and commitment on pastoral work. Bishop of Hippo’s commentaries on the excerpts from the Gospel of John (J 10, 1-17; J 21, 15-17) are basis for the elaboration. Bishop of Hippo indicates that every priest receives his calling from Christ, the Good Shepherd. Thus, he ought to follow Christ and have absolute trust in Him, believing that without God’s grace he can do nothing in his pastoral work. What appears to be especially interesting is St. Augustine’s proposition that even the ministry of an unworthy priest – the evangelical mercenary – can be of a great benefit to the faithful, provided that they will not follow in his footsteps, but merely fulfill the proclaimed Word of God. In the commentaries one can see St. Augustine as a sophisticated exegete, but above all as a zealous priest of the lay faithful and a formation advisor.